1988
DOI: 10.1172/jci113637
|View full text |Cite
|
Sign up to set email alerts
|

Complement induces a transient increase in membrane permeability in unlysed erythrocytes.

Abstract: The effects of low concentrations of human serum on antibody-sensitized sheep erythrocytes (EA) were studied. We report that exposure to low concentrations of serum induced a large but transient increase in the membrane permeability of those EA that do not lyse. This change in the permeability of the erythrocyte membrane resulted in net uptake of Na+ and decrease in cell K+, without affecting the total internal cation content. Although exposure to serum also allowed for net uptake of larger molecules like L-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…On the basis of the present and previous results, we hypothesize that diabetesinduced alternations in enzymatic glycosylations and/or increased formation of advanced glycation end products lead to formation of patterns recognized by MBL. As shown in vitro, complement activation and sublytic formation of the terminal complement complex on mammalian cells may induce release of growth factors, leading to vascular alternations (26)(27)(28)(29)(30)(31). In addition, glycation of complement regulatory proteins has been shown to decrease their regulatory capacity and increase complement activation in diabetes (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the present and previous results, we hypothesize that diabetesinduced alternations in enzymatic glycosylations and/or increased formation of advanced glycation end products lead to formation of patterns recognized by MBL. As shown in vitro, complement activation and sublytic formation of the terminal complement complex on mammalian cells may induce release of growth factors, leading to vascular alternations (26)(27)(28)(29)(30)(31). In addition, glycation of complement regulatory proteins has been shown to decrease their regulatory capacity and increase complement activation in diabetes (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with cells separated by density using Stractan (23). Presumably, Ca2+ also diffuses through the transient complement lesion, which is known to allow for the entry of both Na+ and glucose into the cell (4). Indirect evidence for a role of the Ca2+-induced K+ transport pathway was provided using carbocyanine, a specific inhibitor of this K+ transport pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently reported that under conditions of limited complement activation the MAC may cause a large but transient increase in cell membrane permeability, and the affected cells do not lyse (4). In addition, we also observed that the cells surviving sublytic complement attack do not swell even though they experience a substantial increase in the permeability of their membranes, documented by a marked reduction in intracellular K+ (Kt) and an increase in intracellular Na' (Naj).…”
Section: Introductionmentioning
confidence: 88%
“…A number of investigators have attempted to isolate and identify an endogenous counterpart to the cardiac glycosides from a variety of sources, such as plasma [30 -32, 461, urine [9,10,30], cerebrospinal fluid [47], hypothalamus [I 3,151 and adrenal gland [35]. Although several compounds have been isolated and identified as endogenous substances with the inhibitor activity, most of them have been shown to be nonspecific, low-affinity inhibitors for Na+,K+-ATPase.…”
Section: Discussionmentioning
confidence: 99%